Análisis jurídico y doctrinario del Art. 37 de la Ordenanza Municipal de Loja No 0051- 2022 sobre materiales áridos y pétreos, que se contradice con el Art. 138 y 142 de la Ley de Minería; al establecerse condiciones y obligaciones distintas a la Ley - Condoy Quichimbo, Eddie Patricio (2024)
This Curricular Integration Work focuses on the analysis of a relevant problem in the legal field, which involves the contradiction and disobedience to the hierarchical order of the laws, specifically between the Mining Law and the Municipal Ordinance of the Canton Loja No. 0051- 2022, which generates legal uncertainty and violates the principle of confidentiality of the law. This research focuses on the regulation of the exploitation, transportation and marketing of construction materials in the aforementioned canton of Ecuador, recognizing its fundamental role as a source of income for the local population. Artisanal and small-scale mining is considered a special regime, which must be consolidated and supported, due to its importance in the development of the construction of various works. The central purpose is to support concessionaires and workers involved in the exploitation, transportation and trade of aggregate and stone materials for construction in Loja. To achieve this, it is imperative to establish a legal framework that ensures the adequate imposition of conditions and requirements by the Municipality, as well as compliance with obligations by the mining industry. A discrepancy has been identified in Article 37 of Municipal Ordinance No. 0051-2022, which requires "audited semi-annual production reports", in contravention of Article 142 of the Mining Law, which prohibits establishing obligations other than those already stipulated. ; that is, only annual. Likewise, the provision in the Second Article numbered after Article 138 stands out, which requires production reports must be made with a "sworn declaration" before a Notary before March 31 annually and that does not impose any sanction for their nontimely presentation; It is very easy to cross-reference tax information and establish the fair perception of State benefits, without the need for an Audited Report. With this scenario, the purpose of the research is to outline guidelines to transform municipal regulations, in order to resolve this contradiction and achieve coherent and harmonized regulation